2012
DOI: 10.1088/0031-9155/57/12/3741
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulated correction factors for machine specific reference field dose calibration and output factor measurement using fixed and iris collimators on the CyberKnife system

Abstract: Monte Carlo (MC) simulation of dose to water and dose to detector has been used to calculate the correction factors needed for dose calibration and output factor measurements on the CyberKnife system. Reference field ionization chambers simulated were the PTW 30006, Exradin A12, and NE 2571 Farmer chambers, and small volume chambers PTW 31014 and 31010. Correction factors for Farmer chambers were found to be 0.7%-0.9% larger than those determined from TRS-398 due mainly to the dose gradient across the chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
147
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(168 citation statements)
references
References 30 publications
(12 reference statements)
19
147
1
1
Order By: Relevance
“…SVs have a pitch of 2.5 mm in the square central area of 5 cm side, and a 5 mm pitch outside. In a recent characterization of the device,41 differences between OFs measurements by the 1000SRS, a synthetic diamond (TM60019, PTW) and a small‐field diode (ETM60017, PTW), were approximately 3.0% for a 5 mm collimator and 1.5% for a 7.5 mm collimator, in agreement with previous investigations 26. The size of the SVs (2.3 × 2.3 × 0.5 mm 3 ) would be responsible for the 3% under‐response for the 5 mm collimator owing to volume‐averaging effect 41.…”
Section: Discussionsupporting
confidence: 89%
“…SVs have a pitch of 2.5 mm in the square central area of 5 cm side, and a 5 mm pitch outside. In a recent characterization of the device,41 differences between OFs measurements by the 1000SRS, a synthetic diamond (TM60019, PTW) and a small‐field diode (ETM60017, PTW), were approximately 3.0% for a 5 mm collimator and 1.5% for a 7.5 mm collimator, in agreement with previous investigations 26. The size of the SVs (2.3 × 2.3 × 0.5 mm 3 ) would be responsible for the 3% under‐response for the 5 mm collimator owing to volume‐averaging effect 41.…”
Section: Discussionsupporting
confidence: 89%
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the response of ionization chambers, diodes, and the microdiamond 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 detector in small radiation fields for flattened beams, using either experiment or Monte Carlo simulations. Where necessary, small field correction factors false(kQclinQmsrfclin,fmsrfalse), as defined by Alfonso et al, (18) have been provided.…”
Section: Introductionmentioning
confidence: 99%
“…One useful tool in dealing with small field effect is Monte Carlo (MC) simulation. Many recent studies have applied Monte Carlo simulations to examine the output factors of small field sizes used for radiosurgery such as CyberKnife, 6 , 7 Gamma Knife, 8 , 9 and Brainlab (10) . In addition, numerous studies have used Monte Carlo simulation to examine the accuracy of diode detectors measurements for small field dosimetry 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%